Silencing of LAMC2 Reverses Epithelial-Mesenchymal Transition and Inhibits Angiogenesis in Cholangiocarcinoma via Inactivation of the Epidermal Growth Factor Receptor Signaling Pathway - Pei, Yao-Fei; Liu, Jie; Cheng, Jian; Wu, Wei-Ding; Liu, Xi-Qiang (The American journal of pathology, 2019)
Cholangiocarcinoma (CCA) is a malignant cancer that is associated with high mortality rates. The relationship between laminin γ 2 chain gene (LAMC2) and epidermal growth factor receptor (EGFR) has been previously documented in gastric cancer and oral squamous cell carcinoma. This study investigates the role of LAMC2 in epithelial-mesenchymal transition (EMT) and angiogenesis in CCA and explores the underlying mechanism(s). Differentially expressed genes related to CCA were initially screened using a microarray analysis, and the interaction between LAMC2 and the EGFR signaling pathway was identified. To determine the regulatory effects of LAMC2 on CCA progression, LAMC2 was silenced or overexpressed and the EGFR signaling pathway was activated or blocked. Subsequently, the regulation effects of LAMC2 were evaluated on the expression of EMT markers, invasion and migration of CCA cells, as well as microvessel density in nude mice. Microarray analysis demonstrated that highly expressed LAMC2 is linked to CCA development, which involves the EGFR signaling pathway. When LAMC2 expression was increased, the EGFR signaling pathway and EMT were activated in CCA tissues. Silencing of LAMC2 as well as EGFR signaling pathway inhibition led to suppression of EMT, cell invasion, and migration abilities in vitro, as well as angiogenesis in vivo. This study demonstrates that LAMC2 silencing suppresses the activity of the EGFR signaling pathway, thus functioning as a tumor suppressor in CCA.